Experimental realization of a non-magnetic one-way spin switch - Maren E. Mossman (Nature Portfolio, 2019)
For use in electronic and quantum applications, controlling the magnetism of a system through non-magnetic means is important. Here, the authors demonstrate a unidirectional non-magnetic spin-switch device using spin-momentum coupling in Bose–Einstein condensates of ultracold Rb-87 atoms.